RESEARCH TRENDS IN SMALL AND MEDIUM ENTERPRISES AND ECONOMIC GROWTH: A BIBLIOMETRIC STUDY - Valdyan Drifanda; Kiromim Baroroh; Maimun Sholeh (Universitas PGRI Semarang, 2025)
This study aims to conduct a bibliometric analysis of literature on Micro, Small, and Medium Enterprises (MSMEs) and economic growth. This study analyzes scientific publications indexed in the Scopus database for the period 2020-2025 to map publication trends, identify leading journals and authors, reveal collaboration patterns, analyze citation impact, and identify key research themes. The results show an increase in research activity in this field, with